Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan ada PT Bank Mandiri Persero Tbk. Cabang Bekasi - Amanda Morlian (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
In this study whether job satisfaction and motivation have an influence on employee performance. At the PT. Bank Mandiri Tbk some of the conditions conducive to maintaining employee motivation it's also been a concern by the Division of Human Resources. Among them the opportunity for the selection of career to a higher level, reward program for high performing employees. However, in certain respects it is also still found contradictory condition, which if observed will also be able to potentially reduce even deadly motivation. For example. distinction early retirement age